Tinjauan Yuridis Pailitnya PT. Merpati Nusantara Airlines Persero Akibat Kelalaian Terhadap Perjanjian Damai - Muhammad Rizqy Fajrian; Adi Sulistiyono (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
Law No. 37/2004 on Bankruptcy and PKPU has regulated the bankruptcy and PKPU process for SOEs, where the Ministry of Finance is authorized to file bankruptcy applications. The problem that the author wants to raise regarding the differences in the bankruptcy of BUMN Persero, in this discussion is the bankruptcy case of PT Merpati Nusantara Airlines (PT MNA). Based on the explanation of the Bankruptcy and PKPU Law article 2 paragraph (5), it is stated that BUMNs that can be bankrupted by the minister of finance are BUMNs whose capital is not divided into shares or BUMN Perum, while in practice at the trial the bankruptcy of PT MNA was canceled on the grounds that the BUMN (Persero) could only be bankrupted by the Minister of Finance. Whereas BUMN Persero is subject to the Limited Liability Company Law and is also subject to the Limited Liability Company Law, this is because the arrangements regarding the bankruptcy of BUMN are still overlapping, resulting in inconsistencies in the decisions of judges in examining and deciding BUMN bankruptcy cases. The writing of this article uses normative legal research, using primary legal sources, namely the Bankruptcy Law, Limited Liability Company Law and BUMN Law. The data collection technique in this research is a literature study, namely collecting primary legal materials by tracing laws and regulations related to the position of bankrupt BUMN Persero. Furthermore, secondary legal materials are obtained by collecting books, scientific papers, and journals relevant to the author's research. Using deductive pattern as an analysis method by connecting major and minor premises. The result of this research is that PT MNA, even though it is a Persero SOE and its shares are 100% owned by the government, can still be bankrupted by anyone other than the minister of finance as long as it meets the bankruptcy requirements and the bankruptcy decision of PT MNA which is in accordance with the Bankruptcy and PKPU Law is based on 2 articles of the PKPU Law, namely Article 170 paragraph (1) and Article 291 paragraph (2).